Demographic Bonus for Indonesia: Challenges and Policy Implications of Promoting Universal Health Coverage - Sidayu Ariteja (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2017)
Indonesia has been promoting Universal Health Coverage (UHC) since 2014 as targeted in the national development plan document. Indonesia has also enteredthe stage of demographic bonus that could enhance the benefit of social welfare. Starting from the idea of demographic bonus and the campaign of acceleratingUHC in Indonesia, this paper tries to answer the question of how demographic dividend affects the promotion of UHC declared by the government of Indonesia. Then, this paper analyzes the effects of demographic bonus based on two specific policies, supply-side policy and demand-side policy. The results of the analysis might not directly relate to the issue of demographic bonus. However, it could recommend several suggestions which could deal with the opportunity of demographic bonus. This paper is limited as it only based on some simple calculations on meeting the needs and the gaps on UHC.